Ability, motivation and opportunity to participate in the digital change: A focus group study on new concepts for sustained learning in healthcare organisations - Starke, Sandra; Ludviga, Iveta; Fröhlich, Jonas (Edelweiss Applied Science and Technology, 2025)
The increasing significance of digital health services necessitates a sustained learning process. This study explores the linkage between motivation and the opportunity to actively participate in designing new concepts and competencies, emphasizing sustained learning as a dynamic capability. We conducted two focus group discussions with 21 participants. The collected data were analyzed and categorized using NVivo software. Our findings highlight the applicability of the Ability, Motivation, and Opportunity (AMO) model in digital transformation within healthcare. The role of first movers or early adopters emerges, driving innovation and inspiring broader adoption in the sector. Building digital competencies must be accessible and seamless, ensuring knowledge access and practical learning concepts. We advocate for integrating all stakeholders to foster a shared vision and comprehensive approach to digital implementation. Professional contexts significantly influence motivation, reinforcing the importance of autonomy in selecting learning strategies. This paper theoretically links the AMO Model to dynamic capabilities, clarifying how ability, motivation, and opportunity affect human resources development in healthcare. Relevant stakeholders must be engaged by providing tailored, practice-integrated learning initiatives that align with real-world healthcare challenges.